Prenatal Diagnosis of Down Syndrome Associated with Right Aortic Arch and Dilated Septum Cavi Pellucidi - José Morales-Roselló; Rafael Lázaro-Santander (Hindawi Limited, 2012)
A 30-year-old woman with a normal first trimester Down syndrome screening attended our ultrasound unit for a 20-week scan. The most remarkable anomalies were the presence of a right aortic arch along with a dilated cavum septi pellucidi. In addition, the scan showed an atrioventricular canal and bilateral choroid plexus cysts. Fetal karyotype showed the existence of trisomy 21. A novel association between Down syndrome and dilated cavum septi pellucidi is reported and the relationship between DS and vascular rings is discussed.